Earthquake Iso‐Nuisance and Iso‐Damage Mapping for Alberta: Applications for Choosing Magnitude Thresholds to Manage Induced Seismicity - Mauricio Reyes Canales; Elwyn Galloway; Steven Pawley; Javad Yusifbayov; Greg Hartman (Earth's Future)
Abstract We generate earthquake iso‐nuisance and iso‐damage maps for Alberta. These maps show the spatial distribution of earthquake magnitude required to reach a specific level of nuisance and damage, considering human exposure and surficial geological conditions. We rely on population distribution for the human exposure factor while utilizing Vs30 derived from surficial geological modeling to approximate site amplification effects. By including the trailing seismicity factor, the iso‐nuisance and iso‐damage maps provide the base for the Magnitude Threshold for Acceptable Seismicity maps, which can set a guideline for the upper magnitude boundary, or largest magnitude event permissible, related to industrial activities causing seismicity. The trailing seismicity factor refers to the subsequent seismicity after a substantial change or end of the seismogenic operations; for instance, the cessation of seismogenic hydraulic fracturing activities under a traffic light protocol after a magnitude threshold event (red‐light event). Considering variations in the trailing seismicity factor, we derive different Magnitude Threshold for Acceptable Seismicity maps for various injection‐induced activities, including hydraulic fracturing and fluid disposal activities. Extended versions of the Magnitude Threshold for Acceptable Seismicity maps could allow for safety factors pertinent to critical infrastructure in a particular area, incorporating other factors beyond the population distribution and warranting a different tolerance level. These maps help to define the magnitude threshold from induced seismicity, maintaining the same tolerance levels throughout a region. Thus, they can be highly beneficial in managing current and future cases of induced seismicity related to the energy sector.